Analisis Komparatif Bank Syariah Dan Bank Konvensional Pada Masa Resesi Global COVID-19 - Irvin Ng; Yulfiswandi Yulfiswandi; Junita Junita; Viviani Viviani; Lindawati Lindawati; Joey Joey (STIE Wiyatamandala, 2023)
The popularity of islamic bank has been increasing on countries with Muslims as majority of their population where Muslim consumers could fulfil their banking needs while still complying to their religious rules. Development of islamic banks started from the establishment of Bank Muamalat as the first islamic bank established in Indonesia around 1991. Few studies has shown that islamic banks in Indonesia has better robustness than conventional banks during the 1998 economic crisis. In order to verify that statement, an updated study is required with the latest data and current economic situations. Indonesia has been impacted by the COVID-19 pandemic in which yearly GDP of Indonesia shown a negative growth as the recession status has been attained in the 2nd quarter of 2020. This study is done by comparing islamic banks as well as conventional banks’ fundamentals before and during the pandemic era. It is found that islamic banks is better in overcoming economic crisis than conventional banks. Keywords: Islamic banks, conventional banks, recession, COVID-19